(untitled) (Canadian Dermatology Today, 2020)
There is often a sense of dread when a dermatologist receives a referral for skin picking or excoriations. Due to the nature of our practices, these referrals typically suggest a longer visit, a frustrated patient, and ultimately, a less-than-satisfying visit for all parties involved. How can this be minimized? There are many reasons why a patient might manipulate their skin including an underlying dermatologic condition or neurologic abnormality, pruritus without a rash, medication or drug abuse, and psychiatric illness. As a practicing dermatologist, a patient who presents with an underlying dermatologic condition is relatively easy to identify and diagnose as these cases of skin picking are usually related to an underlying inflammatory dermatosis, infection, or infestation. Similarly, systemic illnesses leading to pruritus without a rash and underlying neurologic abnormality are equally easy to identify and diagnose. An important neurologic condition to rule out, which may lead to skin picking is dementia. The dermatologist should also be familiar with identifying medications and/or recreational drugs of abuse that may lead to itching and subsequent picking. This, then, leaves the category of psychiatric illnesses.